On the Equivalence of Optimality Design Criteria for the Placebo-Treatment Problem - Weng Kee Wong; Holger Dette; Wei Zhu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
We consider a class of optimality criteria and show that each crite- rion has its unique and equivalent dual within the class. This property can be used to find a variety of optimal designs, including a class of compound optimal designs and their relationships. As an example, we show that one type of D-optimal design provides analytical formula for a class of compound optimal designs, while its dual, the more traditional criterion, cannot.
Keywords: 519; Compound optimality; D-optimality; design efficiency; minimax optimality; Experiment; Mathematische Optimierung; Theorie